Different Spectral Hounsfield Unit Curve and High-Energy Virtual Monochromatic Image Characteristics of Squamous Cell Carcinoma Compared with Nonossified Thyroid Cartilage - Forghani, R.; Levental, M.; Gupta, R.; Lam, S.; Dadfar, N.; Curtin, H.D. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: The attenuation of normal nonossified thyroid cartilage can be similar to that of head and neck squamous cell carcinoma on CT. We compared dual-energy CT spectral Hounsfield unit attenuation characteristics of nonossified thyroid cartilage with that of squamous cell carcinoma to determine the optimal virtual monochromatic image reconstruction energy levels for distinguishing tumor from normal nonossified thyroid cartilage.MATERIALS AND METHODS: Dual-energy CT scans from 30 patients with histopathology-proved squamous cell carcinoma at different primary sites (laryngeal and nonlaryngeal) and 10 healthy patients were evaluated. Patients were scanned with a 64-section single-source scanner with fast-kilovolt (peak) switching, and scans were reconstructed at different virtual monochromatic energy levels ranging from 40 to 140 keV. Spectral attenuation curves of tumor and nonossified thyroid cartilage were quantitatively evaluated and compared. Any part of the tumor invading the cartilage, when present, was excluded from ROI analysis to avoid cross-contamination from areas where there could be a mixture of cartilage and invading tumor.RESULTS: Normal nonossified thyroid cartilage had a characteristic, predictable spectral attenuation curve that was different from that of tumors. The greatest difference in attenuation of nonossified cartilage compared with tumor was on virtual monochromatic images of ≥95 keV (P < .0001), with sharp contrast between the relatively high attenuation of nonossified cartilage compared with that of tumor.CONCLUSIONS: Head and neck squamous cell carcinoma has significantly different attenuation on virtual monochromatic images of ≥95 keV, compared with nonossified thyroid cartilage.CNRcontrast-to-noise ratioDECTdual-energy CTHNSCChead and neck squamous cell carcinomaNOTCnonossified thyroid cartilageSHUACspectral Hounsfield unit attenuation curveVMIvirtual monochromatic image